Enhancing Micro-Teaching Through Multimedia: EFL Student Teachers’ Perceptions of Support and Motivation - Cut Eka Mutia; Azizah; Rusmiati (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2026)
This study investigates EFL students’ perceived support and motivation regarding the use of multimedia in micro-teaching classes. The research aimed to explore how multimedia contributes to students’ learning experiences and influences their engagement during teaching practice. A qualitative case study design was employed, involving 10 students enrolled in a micro-teaching class in an English Department of a university in Aceh. Data were collected through non-participant classroom observations and semi-structured interviews, then analyzed using thematic qualitative procedures. The findings reveal that multimedia serves as both instructional and motivational support. Students perceived that multimedia tools such as videos, images, animations, and interactive presentations facilitated clearer material delivery, enhanced conceptual understanding, and increased classroom engagement. Visual and interactive elements helped students connect abstract concepts with practical representations, making lessons more structured and easier to follow. In addition, multimedia significantly improved students’ motivation by creating a more enjoyable and less monotonous learning atmosphere, which encouraged active participation, confidence, and enthusiasm during micro-teaching sessions. The analysis further suggests that the educational value of multimedia is closely related to how it is integrated into the teaching process. These findings imply that micro-teaching courses should guide students to use multimedia in a planned and meaningful way to strengthen both their teaching skills and confidence. Overall, the results suggest that multimedia integration can enrich micro-teaching practices by supporting both cognitive and affective aspects of learning, while highlighting the importance of instructional design competence in technology-enhanced teaching.